The finite element method solution for the right cylindrical tank with non-uniform wall thickness - Maneepai, Satit (1984)
A need exists for the development of the Axi-symmetric Stress Analysis (two-dimensional element) that can be used for static analysis of stress distribution in the bodies of axi-symmetric solid structures under axi-symmetric loading. Such two-dimensional elements are required if it is desired to analyze the right cylindrical tank with linear non-uniform wall thickness under the internal pressure. In this thesis the stiffness matrix for the right cylindrical shell element is derived using the shell theory and cylindrical coordinate system.
The stiffness matrix of two-dimensional element can be generated using standard procedures based on the direct stiffness matrix. The assumed displacement functions are all dependent on the values of the shape functions which are obtained from the linear relationship specifically for two-dimensional quadrilateral shape of elements. These displacement functions are accomplished using interpolation procedure. The examples were solved using the FORTRAN IV programming HP/3000 computer and the solution was found to compare favorably with solution obtained by different finite element meshes.
Thesis (M.S. Civil Engineering)--University of the Philippines, Diliman
Keywords: Finite element method; Structures, Theory of